The Micro, Small and Medium Enterprises Financing Based on Financial Technology - Ica Rika Candraningrat; Vera Intanie Dewi; Nyoman Abundanti; Ni Wayan Mujiati; Badaruz Zaman (Universitas Pendidikan Ganesha, 2022)
Financial technology innovations that are currently developing have provided convenience for the user community in the fields of financial systems, asset management to micro and small business (MSME) financing. The long objective of this research is to optimize the Peer-To-Peer Lending financing model based on the analysis of the preferences of potential lenders in determining MSME financing decisions. This type of research is descriptive quantitative research. Sampling used purposive sampling of MSME actors throughout Bali. The data analysis technique used is logistic regression analysis. The results showed that the estimation model can determine the decision to provide financing to Peer-to-Peer Lending. The variable amount of credit and the term of financing proved to be able to predict financing decisions significantly. While the financing objective variable is not proven to be able to predict financing decisions significantly in Peer-to-Peer Lending financial institutions.